Habitat ecology and diversity of tortoises from Burhi Gandak and Kamla Rivers of Bihar - Kusum Kumari; H.S. Mogalekar; R.K. Ram; R.R. Dupare; P.P Srivastava; S.K. Nayak (Journal of Indian Fisheries Association, 2022)
The study was conducted from May, 2022- July, 2022 to assess the habitat ecology and diversity of tortoises from Burhi Gandak and Kamla Rivers of Bihar. The water velocity of Burhi Gandak river ranged from 3.5 m/s to 5.7 m/s. Similarly, water velocity of Kamla river ranged from 2.6 m/s to 6.5m/s. The average values of water quality parameters from Kamla river was 2.88 mg/l of dissolved oxygen, 7.2 of pH, 132 mg/l of hardness, 225 mg/l of alkalinity, 0.04 mg/l of nitrite and 0.34 mg/l of ammonia. The average values of water quality parameters from Burhi Gandak river was 6.2 mg/l of dissolved oxygen, 7.5 of pH, 141.5 mg/l of hardness, 150 mg/l of alkalinity, 0.1 mg/l of nitrite and 0.0 mg/l of ammonia. The recorded species of tortoise were taxonomically coming under order Testudines, family Geoemydidae for Pangshura tecta (Gray, 1830) (Indian roofed turtle) and family Trionychidae for Lissemys punctate (Bonnaterre, 1789) (Indian flapshell turtle). Among the two observed species, about 18 specimen of Indian roofed turtle and 20 specimens of Indian Flapshell Turtle were studied and released back in their habitat. The Pangshura tecta was recorded only from Kamla river and Lissemys punctate was recorded from both Kamla and Burhi Gandak rivers. The recorded species of tortoise have been marked as Vulnerable in IUCN Red List of threatened species 2023.